Impact of COVID-19 on the treatment of depressive patients in Germany–a gap in care for the mentally ill? - Aichholzer, Mareike; Schiweck, Carmen; Uckermark, Carmen; Hamzehloiya, Tirage; Reif-Leonhard, Christine; Golbach, Rejane; Reif, Andreas; Edwin Thanarajah, Sharmili (Frontiers in Psychiatry, 2023)
Background: The Covid-19 pandemic led to a higher incidence of depression and a worsening of psychiatric conditions, while pre-existing constraints of the healthcare system and safety regulations limited psychiatric care. Aims: We investigated the impact of the pandemic on the clinical care of patients with a single episode (SE-MDD) or major depressive disorder (MDD) in Germany. Methods: Nationwide inpatient data were extracted from the German Institute for Hospital Remuneration System for 2020 and 2021 (depression data) and the Robert Koch Institute (Covid-19 incidence). Changes in inpatients were tested with linear regression models. Local cases of depression in our department compared to 2019 were explored with one-way ANOVA and Dunnett’s test. Results: Across Germany, the inpatient numbers with both SE-MDD and MDD declined by more than 50% during three out of four Covid-19 waves. Higher Covid-19 incidence correlated with decreased inpatient numbers. In our department, fewer MDD inpatients were treated in 2020 (adj. p<0.001) and 2021 (adj. p<0.001) compared to 2019, while the number of SE-MDD inpatients remained stable. During this period fewer elective and more emergency inpatients were admitted. In parallel, MDD outpatient admissions increased in 2021 compared to 2019 (adj. p = 0.002) and 2020 (adj. p = 0.003). Conclusion: During high Covid-19 infection rates, MDD patients received less inpatient care, which might cause poor outcomes in the near future. These data highlight the necessity for improved infrastructure in the in- and outpatient domains to facilitate accessibility to adequate care.